2020
DOI: 10.3389/fpsyt.2020.561464
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Adolescent Residential Mobility and Adult Social Anxiety, BDNF and Amygdala-Orbitofrontal Functional Connectivity in Young Adults With Higher Education

Abstract: Background: Large-scale epidemiological studies demonstrate that house moves during adolescence lead to an increase in anxiety and stress-sensitivity that persists into adulthood. As such, it might be expected that moves during adolescence have strong negative and long-lasting effects on the brain. We hypothesized that moves during adolescence impair fear circuit maturation, as measured by the connectivity between amygdala and orbitofrontal cortex, and expression of brain-derived neurotrophic factor (BDNF).Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One study examining 3700 first‐year university students found that residential mobility in adolescence, but not early childhood, predicted poorer overall mental health and poorer academic performance (Li et al, 2019a). Frequent moving during adolescence is also associated with greater amounts of social anxiety and impedes development of fear circuit maturation and affective regulation (Hasler et al, 2020). Young adults who moved frequently between ages 10 and 16 had lower concentrations of brain‐derived neurotrophic factor (BDNF), which plays a central role in the development of the prefrontal–amygdala circuit during adolescence, and more abnormal amygdala–orbitofrontal functional connectivity later on, increasing the risk of social deficits.…”
Section: Psychological Implications Of Residential Mobilitymentioning
confidence: 99%
“…One study examining 3700 first‐year university students found that residential mobility in adolescence, but not early childhood, predicted poorer overall mental health and poorer academic performance (Li et al, 2019a). Frequent moving during adolescence is also associated with greater amounts of social anxiety and impedes development of fear circuit maturation and affective regulation (Hasler et al, 2020). Young adults who moved frequently between ages 10 and 16 had lower concentrations of brain‐derived neurotrophic factor (BDNF), which plays a central role in the development of the prefrontal–amygdala circuit during adolescence, and more abnormal amygdala–orbitofrontal functional connectivity later on, increasing the risk of social deficits.…”
Section: Psychological Implications Of Residential Mobilitymentioning
confidence: 99%
“…The OFC is responsible for top-down processes, exerting cognitive control by reducing automatic responses from the amygdala [ 44 , 45 ]. In young adults with social anxiety, an altered amygdala–orbitofrontal functional connectivity explains the effort of the PFC to control amygdala overactivity [ 46 ]. On the other hand, according to the fear network model, the insula integrates interoceptive information [ 47 ].…”
Section: Discussionmentioning
confidence: 99%